Evaluation of Electromyographic Activity of Masticatory Muscles in Adults with Posterior Crossbite - Luiz Makito Osawa Gutierrez; Melissa Coradini Quatrin; Chiarella Sforza; Rafael Reimann Baptista; Eduardo Martinelli Santayana de Lima (Hindawi Limited, 2022)
Introduction. There is evidence that patients with posterior crossbite (PXB) have neuromuscular changes in the masticatory muscles. However, up to the present time, the relationship among these changes on the electromyographic activity of the masticatory muscles is still unclear. Objective. To systematic review the available literature on the electromyographic activity of masticatory muscles in adults with PXB. Methods. Between August 22 and September 9, 2020, we searched the following seven electronic databases: PubMed, EMBASE, Web of Science, Cochrane Library, SciELO, LILACS, and Scopus. No restrictions were applied regarding the language and year of publication. This systematic review was registered in the Prospective Register of Systematic Reviews (PROSPERO - CRD42020205057) database and conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. After data selection and extraction, the methodological quality of the selected studies was conducted independently by two reviewers, using two different evaluation tools. Results. 6957 records were initially located after the search process. In the end, eight papers were selected. Most studies were classified as having average to low methodological quality and moderate to high risk of bias. Based on the available evidence, adult patients with PXB have electromyographic activity changes in the masticatory muscles when compared with individuals without PXB. Moreover, adult patients with unilateral posterior crossbite (UPXB) have asymmetrical electromyographic activity when the crossbite side is compared with the noncrossbite side. Conclusion. Despite the lack of studies with high methodological quality, electromyographic evaluation of masticatory muscles should be considered in the diagnosis and in the orthodontic treatment plan of patients with PXB. Prospective studies with a higher sample size and follow-up time, conducted using a rigorous scientific methodology, are necessary to reach a more reliable conclusion.